What are the effects of severe visual impairment on the cortical organization and connectivity of primary visual cortex? - DeLaine D Larsen; Julie D Luu; Marie E Burns; Marie E Burns; Leah Krubitzer; Leah Krubitzer (Frontiers Media S.A., 2009)
The organization and connections of the primary visual area (V1) were examined in mice that lacked functional rods (Gnat-/-), but had normal cone function. Because mice are nocturnal and rely almost exclusively on rod vision for normal behaviors, the Gnat-/- mice used in the present study are considered functionally blind. Our goal was to determine if visual cortex is reorganized in these mice, and to examine the neuroanatomical connections that may subserve reorganization. We found that most neurons in V1 responded to auditory, or some combination of auditory, somatosensory, and/or visual stimulation. We also determined that cortical connections of V1 in Gnat-/- mice were similar to those in normal animals, but even in normal animals, there is sparse input from auditory cortex to V1. An important observation was that most of the subcortical inputs to V1 were from thalamic nuclei that normally project to V1 such as the lateral geniculate (LG), lateral posterior (LP), and lateral dorsal (LD) nuclei. However, V1 also received some abnormal subcortical inputs from the anterior thalamic nuclei, the ventral posterior, the ventral lateral and the posterior nuclei. While the vision generated from the small number of cones appears to be sufficient to maintain most of the patterns of normal connectivity, the sparse abnormal thalamic inputs to VI, existing inputs from auditory cortex, and possibly abnormal inputs to LG and LP may be responsible for generating the alterations in the functional organization of V1.